In Search of Concepts: The Eﬀects of Speculative Demand on Stock Returns. (30th July 2015) - Gwilym, Owain Ap; Hasan, Iftekhar; Wang, Qingwei; Xie, Ru
Abstract: Using a novel proxy of investors' speculative demand constructed from online search interest in investment concepts, we examine how speculative demand aﬀects the returns of Chinese stocks. We find that speculative demand increases following high market returns and predicts subsequent return reversals. Moreover, the speculative demand explains more variation in subsequent returns of A shares (more populated by retail investors) than B shares (less populated by retail investors). Our findings support the recently developed attention theory.